2002
DOI: 10.1017/s0954579402002018
|View full text |Cite
|
Sign up to set email alerts
|

The temporal binding deficit hypothesis of autism

Abstract: Frith has argued that people with autism show "weak central coherence," an unusual bias toward piecemeal rather than configurational processing and a reduction in the normal tendency to process information in context. However, the precise cognitive and neurological mechanisms underlying weak central coherence are still unknown. We propose the hypothesis that the features of autism associated with weak central coherence result from a reduction in the integration of specialized local neural networks in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
249
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(286 citation statements)
references
References 32 publications
(23 reference statements)
27
249
0
5
Order By: Relevance
“…As noted in our introduction, this conclusion is in line with increasing evidence suggesting that ASD may be characterised by an underconnectivity of disparate brain regions (e.g. Belmonte et al, 2004;Brock et al, 2002;Rippon et al, in press). The only direct evidence for this suggestion to date stems from functional imaging studies involving tasks assessing sentence comprehension (Just et al, 2004), executive function (Just et al, in press), working memory (Koshino, Carpenter, Minshew, Cherkassky, Keller & Just, 2005) and mental state attribution (Castelli et al, 2002), all of which concluded that intra-cortical connectivity is atypical in ASD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As noted in our introduction, this conclusion is in line with increasing evidence suggesting that ASD may be characterised by an underconnectivity of disparate brain regions (e.g. Belmonte et al, 2004;Brock et al, 2002;Rippon et al, in press). The only direct evidence for this suggestion to date stems from functional imaging studies involving tasks assessing sentence comprehension (Just et al, 2004), executive function (Just et al, in press), working memory (Koshino, Carpenter, Minshew, Cherkassky, Keller & Just, 2005) and mental state attribution (Castelli et al, 2002), all of which concluded that intra-cortical connectivity is atypical in ASD.…”
Section: Discussionsupporting
confidence: 89%
“…responding to the conditioned stimulus but not to the non-conditioned stimuli). Since several lines of evidence indicate that ASD may be characterised by poor connectivity between disparate brain regions (Belmonte, Allen, BeckelMitchener, Boulanger, Carper & Webb, 2004;Ben Shalom, 2000;Brock, Brown, Boucher & Rippon, 2002;Castelli, Frith, Happe & Frith, 2002;Just, Cherkassky, Keller & Minshew, 2004;Just, Cherkassky, Keller, Kana & Minshew, in press;McAlonan, et al, 2005;Rippon, Brock, Brown & Boucher, in press), an investigation of differential fear conditioning in ASD may provide valuable behavioural insights into the functional integrity of cortico-amygdala connectivity in this population.…”
Section: Introductionmentioning
confidence: 99%
“…They also sometimes struggle to recall where, when, how or from whom they learnt something (Bowler, Gardiner, & Berthollier, 2004;Bennetto et al, 1996), and both neural and theoretical perspectives suggest that individuals with ASD experience difficulties in binding elements of an experience together in memory (e.g. Bowler et al, 1997;Brock, Brown, Boucher, & Rippon, 2002;Parkin, 1997). Moreover, neural approaches implicating the frontal lobes in the neuropathology of ASD would lead to the prediction that such individuals would have an increased tendency to confabulate (e.g.…”
Section: Permanent Repository Linkmentioning
confidence: 99%
“…Castelli et al (2002) reported a similar measure of functional underconnectivity in a PET study, but during performance of a theory of mind task rather than in a resting state. Thus, a number of functional neuroimaging studies suggest that there is a lower level of coordination among brain areas in autism, and a number of articles have commented on the viability of some form of connectivity account of autism (e.g., Brock et al 2002;Frith 2003;Belmonte et al 2004;Just et al 2004;Courchesne and Pierce 2005;Rippon et al 2006).…”
Section: Introductionmentioning
confidence: 99%